Georg Cantor and idea of the unity of science - Dadaczyński, Jerzy (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2009)
G. Cantor presented - in an unpublished paper (1884) - a vision of the unity of science. He argued all sciences can be reduced directly to the set theory. A source of this idea was for Cantor the unity of mathematics (on the basis of set theory). Cantor represented thesis about the unity of science irrespective of the representatives of positivism (E. Mach).